Pharmacokinetics of plasma‐derived vs. recombinant FVIII concentrates: a comparative study. (2nd October 2014) - Morfini, M.; Marchesini, E.; Paladino, E.; Santoro, C.; Zanon, E.; Iorio, A.
Summary Only very few pharmacokinetic (PK) studies comparing plasma derived FVIII (pd‐FVIII) against recombinant FVIII (rFVIII) concentrates are available. The studies have been generally conducted to demonstrate the bioequivalence of a new product with an old one. The switch from a plasma‐derived FVIII (pd‐FVIII) to a rFVIII concentrate is a good moment to enrol the patients in a comparative PK study. To achieve information on the PK characteristics of two different classes of FVIII concentrates, according to two different designs: a 10 FVIII concentration/time point design and a reduced 4‐point design. A single dose PK comparing pd‐ and rFVIII concentrates has been performed in four Haemophilia Centres of Italy. Seventeen haemophilia A patients underwent two subsequent single dose PK studies at the moment of switching. Two‐compartment‐ and Non‐compartment‐analysis did not show significant differences between the outcomes of PK of pd‐FVIII and rFVIII, due to inter‐patient variability. In vivo recovery (IVR) of rFVIII was slightly higher than that of pd‐FVIII and rFVIII/pd‐FVIII AUC ratio was 1.37 in 11/17 patients. The difference is only due to the initial distribution phase because after the first 10 h from the end of the infusion, the two decay curves are overlapping. The elimination half‐life of the concentrates was very similar even though a complete bioequivalence was not demonstrated because of a higher AUC of rFVIII concentrates, limited to the distribution phase. The higher Cmax and IVR of rFVIII may be due to the presence of heterodimers activated forms of the recombinant molecules.